Efficient Non-Invasive Plasmid-DNA Administration into Tibialis Cranialis Muscle of “Little” Mice - R. Cecchi, C.; Higuti, E.; R. Lima, E.; P. Vieira, D.; L. Squair, P.; N. Peroni, C.; Bartolini, P. (Current Molecular Medicine, 2017)
Background: An alternative treatment for growth hormone deficiency based on hGH-DNA administration, followed by electro gene transfer, was investigated by injecting the plasmid into surgically exposed or non-exposed quadriceps or tibialis muscle of immunodeficient “little” mice. Methods: An optimization of electrotransfer conditions via a new combination of high/low voltage pulses is presented. After 3 days, serum hGH was determined and in a 28-day assay, the relative growth parameters were compared. Results: Both groups exhibited similar results: 5.0 ± 2.2 (SD) and 3.5 ± 0.9 ng hGH/ml (P>0.05; n=7) for the exposed quadriceps and non-exposed tibialis treatments, respectively. The final body weight increases were 16.1% for the quadriceps and 18.9% for the tibialis group. The tail and nose-to-tail length increases were 4.5% and 7.1% for the quadriceps and 4.8 and 4.6% for the tibialis group. The right and left femur length increases, obtained from radiographic measurements, were 16.9% and 12.7% for the quadriceps and 19.4% and 12.3% for the tibialis, respectively. A non-significant difference between exposed quadriceps and non-exposed tibialis treatments (P=0.48) was confirmed via a completely integrated statistical analysis. Circulating mIGF-1 levels were 126 ± 47, 106 ± 93 (P>0.05) and 38 ± 15 ng/ml for the quadriceps, tibialis and saline treatments, respectively. Conclusion: These results show that hGH-DNA administration into non-exposed tibialis muscle followed by the new HV/LV electrotransfer protocol was an equally efficient, less traumatic treatment, much more suitable for pre-clinical testing than administration into exposed quadriceps.
Keywords: serum mIGF-1 levels